PERBANDINGAN HASIL BELAJAR SHOOTING BOLABASKET MELALUI PEMBELAJARAN INKUIRI DAN PENGAJARAN BERDASARKAN MASALAH (STUDI PADA SISWA KELAS VIII SMP NEGERI 1 LENTENG SUMENEP) - NURDIANSYAH, ZIDQI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Study in playing basketball is one of sport branches which is included in the curriculum education in the school. So that, in order to make students attracted to study basketball playing is needed many kinds of model learning`s and attractive for students to make them fun and happy so students interest to study basketball playing especially to increase a mastery of Under Basket Shoot technique. Some teaching models in physical education that can be applied is Inquiry Learning and Teaching Based On Problems Model. Every learning model has advantages and weakness which can influence learning process and result of study. Because of it a teacher must be able to have a mastery of materials and choose learning model based on the students characteristic, so learning process can be more effective and can increase the result of study well. The objectives study of this research are : (1) the differences of the result of study Under Basket Shoot for basketball by inquiry learning and teaching based on problems. (2) the big differences of the result of study Under Basket Shoot for basketball by inquiry learning and teaching based on problems. The subject of study in this research is eighth grade of SMP Negeri 1 Lenteng Sumenep. They are 58 (fifty eighth) students who divided into two groups. The first group is 29 students and second group is 29 students. The method that is used to analyzed the data is statistic descriptive quantitative and comparative method. The conclusion of this research is : (1) there is significant difference between the result of study Under Basket Shoot when students study basketball by inquiry learning and teaching based on problems. The result of difference average test for every group shows that value tcount  3,349 > ttable 2,0. (2) inquiry learning model in fact can increase the result of study under basket shoot for students basketball it is 56,1 % while teaching based on problems can increase the result study under basket shoot for basketball 46,3%. In other words, it can be said that inquiry learning model can increase the result of study under basket shoot for basketball better than teaching based on problems. Keywords: Learning, Inquiry, Based on Problems, Under Basket Shoot, Basketball.